2009
DOI: 10.1111/j.1099-0860.2009.00239.x
|View full text |Cite
|
Sign up to set email alerts
|

What Not to Wear? Girls, Clothing and ‘Showing’ the Body

Abstract: Consumption practices of children in contemporary Western societies are implicated in the reconstruction of childhood, according to both popular debate and to those academic perspectives stressing the individualisation of identities within the life course of late modern consumer societies. Yet, little is known about the meanings children themselves give to their own consumption. Drawing from an ethnographic study of children aged 6–11 years and their families, the paper presents girls’ constructions of fashion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
(21 reference statements)
1
12
0
5
Order By: Relevance
“…Our findings are consistent with prior research on the doing of gender and age through fashion among pre-teens and their understanding of apparently sexualised clothing, which warn against interpretations of sexualisation as a linear cause-effect process (Pilcher, 2010;Rysst, 2010 Like Barbie before them, these games introduce tweens to a highly stereotypical model of adult femininity; in continuity with Barbie, moreover, dress up games "not only are gendered but are also a game about gender" and age (Driscoll, 2005: 226). From the one side, these games introduce young girls to an ageless girl culture where beauty practices, body makeovers and shopping play a fundamental role in building a post-feminist identity that fit from tweens to women in their 30s and 40s.…”
Section: Consumer Culture Media Culture and Gender Identitysupporting
confidence: 90%
“…Our findings are consistent with prior research on the doing of gender and age through fashion among pre-teens and their understanding of apparently sexualised clothing, which warn against interpretations of sexualisation as a linear cause-effect process (Pilcher, 2010;Rysst, 2010 Like Barbie before them, these games introduce tweens to a highly stereotypical model of adult femininity; in continuity with Barbie, moreover, dress up games "not only are gendered but are also a game about gender" and age (Driscoll, 2005: 226). From the one side, these games introduce young girls to an ageless girl culture where beauty practices, body makeovers and shopping play a fundamental role in building a post-feminist identity that fit from tweens to women in their 30s and 40s.…”
Section: Consumer Culture Media Culture and Gender Identitysupporting
confidence: 90%
“…Indeed, Buckingham and Bragg's () analysis of interview and diary data of 120 nine to 17 year olds demonstrated that children and young people assert agency in interpreting and assimilating sexual messages that they are exposed to through adult and youth media. Rysst () and Pilcher () have also demonstrated how adult interpretations of girls’ fashion are frequently at odds with adult interpretations in that adults assume that girls want to look ‘sexy’ and provocative whereas the girls talk about wishing to look ‘grown up’ and ‘cool’. Thus, children appear to assert agency and interpret ‘adult’ materials in more complex and nuanced ways than adults frequently assume (Renold ; Wyness ).…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary studies indicate that tweens are not passive receivers regarding the construction of their identities, but they themselves actively participate in this process [1][2][3][4]. More recent studies highlight the strong bond between mother and daughter in pre-adolescence [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%